السرية والاستيقان في النظم الآلية المتكاملة للمكتبات - عثمان، فارس علي محمد (جمعية المكتبات والمعلومات الأردنية, 2018)
The study deals with two of automated integrated library system criteria in respect to Confidentiality and Authenticity. It aims at calculating the degree of suitability of Evergreen system for public libraries in light of these two criteria. Content analysis research method was used through _Fuzzy Logic_ depending on a refereed content analysis tool, developed by the researcher, representing the “Jordanian Standards” for the evaluation of automated library systems. Result indicated that the degree of suitability of Evergreen system for public libraries in light of these two criteria, using _Fuzzy Logic_ was equal to 0.8. This value indicates that Evergreen system has a high ability in keeping data Confidentiality, and good Authenticity for proofing resources and personal identity. The study recommends the necessity of calculating the degree of suitability of Evergreen system for public libraries with respect to Security criteria, or all Jordanian Standards. Furthermore, this study suggested that future studies should not be restricted to Evergreen system, per se, for helping public libraries making decisions related to the most suitable automated integrated system.
تتناول الدراسة معيارين مهمين من معايير أمن النظم الآلية في المكتبات وهما السرية (Confidentiality) والاسيقان (Authenticity)، وهدفت إلى حساب درجة ملاءمة نظام إفرغرين للمكتبات العامة في ضوء معياري الاستيقان وسرية البيانات في النظم الآلية للمكتبات، وانتهجت الدراسة أسلوب تحليل المحتوى باستخدام المنطق الضبابي Fuzzy Logic، واعتمادا على أداة تحليل محتوى محكمة، ومعدة مسبقا من الباحث، تمثل المعايير الأردنية لتقييم النظم الآلية للمكتبات. وأظهرت النتائج أن درجة ملاءمة نظام إفرغرين للمكتبات العامة في ضوء معياري السرية والاستيقان تساوي 0.8 حسب المنطق الصبابي، وتشير هذه القيمة إلى أن نظام إفرغرين يتمتع بقدرة عالية على المحافظة على سرية البيانات، وقدرة جيدة على الاستيقان أو إثبات معرف وهوية الموارد والأشخاص، وقد أوصت الدراسة بضرورة حساب درجة ملاءمة نظام إفرغرين للمكتبات العامة في ضوء كافة مجموعات المعايير الأردنية أو مجموعة الآمن على الأقل، وأن لا تقتصر الدراسات في المستقل على نظام إفرغرين فقط، بهدف مساعدة المكتبات العامة في اتخاذ القرار المتعلق باستخدام نظام آلي مناسب في حوسبة مقتنياتها.
Keywords: المكتبات العامة; أمن النظم الآلية; أتمتة المكتبات; نظم المعلومات